Evaluation and optimization of a novel cascade refrigeration system driven by waste heat - Zheng, Weibo; Zhou, Hongbin; Xiao, Zhiyong; Sun, Dong; Song, Changshan; Zhang, Xiaohan; Li, Jianbo (Frontiers in Energy Research, 2023)
Direct discharge of waste heat from the internal combustion engine (ICE) is unfavorable to efficient and clean fuel utilization. Here, a novel combined absorption-compression cascade refrigeration cycle is proposed to efficiently utilize low-grade waste heat and supply cooling capacity for food freezing in vessels or refrigerated trucks. The intention of this work lies in: i) Comprehensively evaluating the performances of the proposed system; ii) Gaining the optimal operating conditions of the system. Aimed that, analysis models of energy, exergy, economy, and environment are set up to evaluate their sweeping performances. Further, multi-objective optimization is introduced to obtain the optimal operating parameters including evaporation and condensation temperature of the low-temperature stage, condensation temperature of the high-temperature phase, and cascade temperature differences. By applying multi-objective optimization, the COP of the system can reach 1.547, exergy efficiency can reach 0.246, the discharge amount of carbon dioxide declines from 71.40 to 59.57 tons•year-1, and annual total cost decreases from 16028 to 15055 •year-1 compared to initial design conditions.